Persepsi Pasien BPJS Rawat Jalan dengan Kualitas Pelayanan Petugas Kesehatan di Puskesmas Mawasangka Timur - Nur Hudayah; Rininta Andriani; Setiawati Setiawati (Sarana Ilmu Indonesia (salnesia), 2019)
The quality of health services is that refers to the level of perfection of health services, which one party can lead to satisfaction with each patient. The aim of the study was to determine the relationship of patient’s perception based on age, sex, education level, and knowledge with quality of health care services in the East Mawasangka. This type of research was observational analytic with cross sectional study approach. Sample in this study were 160 patients who came for treatment with BPJS Health status. The sampling technique using total sampling. Data were tested using chi-square. Based on the results of research shows that there is a relationship between patient’s perception based on age and health service quality (p = 0,043). There is no relationship between patient’s perception based on sex (p = 0,066), education level (p = 0,071) and knowledge( p = 0,071) with the quality of health workers in the East Mawasanka Health Center. It is recommended that there is a need for cooperation among health workers so that the utilization of services is carried out properly.